Analisa Penerapan Manajemen Marketing Komunikasi Radio Urban 106.3 Fm dalam Mempertahankan Pengiklan (Studi Kasus Pada Radio Urban Bandung 106.3 Fm) - Rifky Akmal Padhilah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze the implementation of Urban Radio Communications 106.3 fm marketing manajemen in maintaining advertisers. This research is a qualitative research. In this study, researchers used a case study approach to reveal the implementation and problems in the implementation of Urban Radio 106.3 fm marketing communication manajemen in retaining advertisers through interviews, observation, and documentation. The results of this study indicate that Urban Radio implements 90% of the implementation of marketing communication management based on theory. This makes Radio Urban more mature in preparation and in technical terms of implementation and has targets to evaluate. Apart from that, Urban Radio also improvises the technical implementation according to how comfortable the executor is. This is a determining factor for Urban Radio’s success in surviving and being able to compete with other radios. Community marketing allows us to go beyond traditional marketing tactics and reach potential customers. This is because the internet includes technology that influences and touches human life so much.